2005
DOI: 10.1159/000088923
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-8 Is a Powerful Prognostic Predictor of All-Cause and Cardiovascular Mortality in Dialytic Patients

Abstract: Background: Cohort studies have demonstrated an association between C-reactive protein (CRP) and interleukin-6 (IL-6) and all-cause and cardiovascular mortality in end-stage renal disease (ESRD) patients. Interleukin-8 (IL-8) appears to be not only the plasma expression of the acute-phase response but also a direct pathogenetic mediator of the atherosclerotic process. Methods: To evaluate the role of IL-8 in predicting outcome, 76 chronic dialytic patients were prospectively followed for 18 months. At baseline… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
34
0
5

Year Published

2006
2006
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(41 citation statements)
references
References 62 publications
2
34
0
5
Order By: Relevance
“…This may be due to the known sources of IL-8 production, which are mainly linked to cells other than the endothelial cells. Moreover, the paradoxical associations between in vitro and in vivo findings as well as between IL-8, FMD and IMT contrast with previous studies and deserve further investigation [29]. …”
Section: Discussionmentioning
confidence: 61%
“…This may be due to the known sources of IL-8 production, which are mainly linked to cells other than the endothelial cells. Moreover, the paradoxical associations between in vitro and in vivo findings as well as between IL-8, FMD and IMT contrast with previous studies and deserve further investigation [29]. …”
Section: Discussionmentioning
confidence: 61%
“…In addition, many non-gout-focused studies showed a role for CXCL8 in predicting CVD. CXCL8 functions as an independent predictor for clinical outcome in patients with coronary artery disease (34) and for CVD in patients with end-stage renal disease (35). Finally, CXCL8 was found to be increased in diabetes mellitus and was suggested to be a marker linking obesity with metabolic complications such as atherosclerosis and diabetes mellitus (11).…”
Section: Discussionmentioning
confidence: 98%
“…Alterations in monocytes and monocyte-derived cytokines have been implicated in the inflammatory pathology that exists in ESRD. 39,41,44,48,49 IL-8, IL-6, and TNF-␣ are possible direct mediators in the pathogenesis of atherosclerosis. 50 -58 In addition, there seems to be a significant correlation between the level of these various cytokines and patient outcomes, with multiple studies suggesting that elevations in IL-8, IL-6, and TNF-␣ levels are associated with increased morbidity and mortality in patients with ESRD.…”
Section: Discussionmentioning
confidence: 99%